Consequences of the exposure to bisphenol A in cell membrane models at the molecular level and hamster ovary cells viability - Maximino, Mateus D. [UNESP]; Silva, Carla Y. [UNESP]; Cavalcante, Dalita G.S.M. [UNESP]; Martin, Cibely S. [UNESP]; Job, Aldo E. [UNESP]; Oliveira, Osvaldo N.; Aléssio, Priscila [UNESP] (Elsevier, 2021)
The inadequate disposal and the difficulty in its removal from water treatment systems have made the endocrine disruptor bisphenol A (BPA) a significant hazard for humans and animals. The molecular-level mechanisms of BPA action are not known in detail, which calls for systematic investigations using cell membrane models. This paper shows that BPA affects Langmuir monolayers and giant unilamellar vesicles (GUVs) of 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC) used as membrane models, in a concentration-dependent manner and with effects that depend on BPA aggregation. BPA increases DPPC monolayer fluidity in surface pressure isotherms upon interacting with the headgroups through hydrogen bonding, according to polarization-modulated infrared reflection absorption spectroscopy (PM-IRRAS). In DPPC GUVs, BPA induced wrinkling and distortion in the spherical shape of the vesicles, but this was only observed for fresh solutions where it is not aggregated. BPA also decreased the viability of hamster ovary cells (CHO) in in vitro experiments. In contrast, aged, aggregated BPA solutions did not affect the GUVs and even increased CHO viability. These results may be rationalized in terms of size-dependent effects of BPA, which may be relevant for its endocrine-disrupting effects.
Keywords: Bisphenol A; Cell membrane models; Cell viability; Endocrine disruptors; Langmuir monolayers; Vesicles